A Psychological Journey of Inner Strength in Novel Mimpi Anak Pulau - Anita, Anita; Harpriyanti, Haswinda (Cultural Narratives, 2024)
This research analyzes the fighting values of the main character of the novel Mimpi Anak Pulau through a literary psychology approach. The focus of the research is mainly on the main character's inner resilience, exploring how the character adapts and develops in facing various life challenges. The analysis also includes the diversity of internal human resources, especially through the inner eye and mind's eye, as an important element in forming character. Carefully selected dialogue creates dimensions of internal conflict, reveals the characters' complex feelings, and touches on the paradox between fear and courage. Poetry that compares life to a flowing stream creates a picture of life's journey that inspires thought and emotion. The research conclusion shows that the fighting value in the main character of this novel is realized through a complex psychological journey, contributing to a deeper understanding of inner resilience, diversity of internal resources, and psychological dynamics in a literary work. This analysis not only highlights the complex psychological processes underlying the main character's resilience in Mimpi Anak Pulau, but also offers valuable insights for understanding how children develop inner strength in the face of adversity. By examining the character's internal resources and the role of literary devices in portraying inner conflict, this study provides educators and psychologists with tools to support children's emotional well-being and foster resilience.